Feedback Control and Parameter Invasion for a Discrete Competitive Lotka–Volterra System - Li Xu; Shanshan Lou; Panqi Xu; Guang Zhang (Discrete Dynamics in Nature and Society)
State feedback is used to stabilize the Turing instability at the unstable equilibrium point of a discrete competitive Lotka–Volterra system. In addition, a regularization method is applied to parameter inversion for the given Turing system and numerical simulation can verify the effectiveness of the algorithm. Furthermore, how less or more sample data and dependence on the initial state affect estimation procedure are tested.